ELECTRONIC PORTFOLIO AS A MEANS OF FORMING COMPETENCE OF FUTURE TEACHERS - Turganbayeva, А.Р.; Turgantay, А.Ә. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2022)
In the conditions of the modern information society, the digital industry is developing, modernized high-tech computer tools and communication systems are rapidly being introduced into the field of education, and new requirements are imposed on the training of teachers. In the context of the rapid spread of information and communication technologies (ICT) and the informatization of education, one of the main tasks of modern higher education is to prepare students for the digital economy of the future. The article describes the goals of creating an electronic portfolio of students - future teachers. The article discusses the pedagogical issues of creating an electronic portfolio in a university, its content, tasks, and functions. Foreign and domestic pedagogical studies on the experience of using an electronic portfolio are analyzed. The main types of portfolios are highlighted. Special attention is paid to the aggregation method based on a portfolio of effective data on the professional competence of future specialists.